2019
DOI: 10.3389/fpsyg.2019.00639
|View full text |Cite
|
Sign up to set email alerts
|

Deposit Limit Prompt in Online Gambling for Reducing Gambling Intensity: A Randomized Controlled Trial

Abstract: Pre-commitment tools – allowing users of gambling services to pre-set a limit for how much money they may spend – are relatively common. However, there exist no clear evidence of their effectiveness in preventing gamblers from spending more money than they otherwise planned. The aim of the study was to compare gambling intensity between users of an online gambling service prompted to set a deposit limit and non-prompted customers, both in the whole sample and among most active users based on the total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…The increased percentage of players using the voluntary money setting feature in the present study may purely be because such RG features are now more embedded in modern online gambling websites and/or are more advertised to players within-site than they were 10 years ago. The percentage of 8.3% of players setting a voluntary limit in the present study was similar to that to the recent study by Ivanova et al (2019) who found that 6.5% of newly registered players set a voluntary limit 90 days after registration without actively being prompted by the operator to do so. In each of the ten playing intensity groups in the present study, the percentage of active players in the first quarter of 2017 was higher in the group of players who had set voluntary money limits in the first quarter of 2016 compared to players that did not.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased percentage of players using the voluntary money setting feature in the present study may purely be because such RG features are now more embedded in modern online gambling websites and/or are more advertised to players within-site than they were 10 years ago. The percentage of 8.3% of players setting a voluntary limit in the present study was similar to that to the recent study by Ivanova et al (2019) who found that 6.5% of newly registered players set a voluntary limit 90 days after registration without actively being prompted by the operator to do so. In each of the ten playing intensity groups in the present study, the percentage of active players in the first quarter of 2017 was higher in the group of players who had set voluntary money limits in the first quarter of 2016 compared to players that did not.…”
Section: Discussionsupporting
confidence: 91%
“…Among a sample from 100,000 online players at win2day, Auer and Griffiths (2013) found that deposit limits subsequently decreased gambling expenditure among casino and lottery players, and that time limits decreased gambling expenditure among poker players. More recently, in a real-world experimental study with 4328 players from an European online gambling operator, Ivanova et al (2019) found that newly registered players were more likely to set voluntary limits if they were actively prompted by the gambling operator to do so. However, players who set voluntary limits without being prompted to do so lost more money gambling than players who did not set limits.…”
Section: Online Gambling Limit-setting and Behavioural Trackingmentioning
confidence: 99%
“…Using a matched-pairs design, the study showed that among the players overall, receiving the message significantly reduced their gambling expenditure 3 months later. Ivanova et al (2019) compared the gambling intensity between users of an online gambling service prompted to set a deposit limit and non-prompted customers. They found that prompting online gamblers to set a voluntary deposit limit of optional size did not affect subsequent net loss compared to unprompted customers, who set deposit limits without being prompted.…”
Section: Limit-setting Tools In Gambling Environmentsmentioning
confidence: 99%
“…For instance, 13 of the 14 CBT studies included in a Cochrane review of psychological treatments for gambling disorder included a measure of financial losses (Cowlishaw et al, 2012). These reports can be self-reported using diary-type methods, such as the timeline follow-back (TLFB; Weinstock, Whelan, & Meyers, 2004), or using singleitem scales, or be based on real player data, e.g., when a responsible gambling intervention is evaluated in collaboration with the industry (Auer & Griffiths, 2016;Ivanova, Magnusson, & Carlbring, 2019;Jonsson, Hodgins, Munck, & Carlbring, 2019). Behavioral measures commonly focus on days gambled and net money lost, which are thought to capture the majority of negative consequences associated with excessive gambling (Walker et al, 2006, p. 505).…”
mentioning
confidence: 99%
“…Unfortunately, the issue of missing data is generally a big concern in gambling intervention studies (Grant, Kim, & Kuskowski, 2004;Hodgins, Stea, & Grant, 2011;Westphal, 2008). In a review of psychological treatments Melville, Casey, and Kavanagh (2007), found that the dropout ranged from 14% to 50%, with a median of 26%.…”
mentioning
confidence: 99%